A Syntactic Analysis of Various Texts: An Examination of Sentence Structure, Clause Patterns, and Frequent Errors - Nabila Aprilia; Fransiska, Angel Bella; Putri, Salsabila Nadhifah; Al-Kautsar, Muhammad Faiz; Aprizal (Global Expert: Jurnal Bahasa dan Sastra, 2024)
Syntax is a critical component of language study, as it facilitates comprehension of linguistic complexity and enhances communication. This paper explores syntactic aspects, sentence structure, text analysis,  and clause patterns across a variety of texts, thereby establishing a link between theoretical linguistics and practical applications. The book's approach contributes to the field of education by equipping students with the analytical skills necessary to comprehend language, thus leading to the development of their communication and critical thinking abilities. Keywords: Syntax, Text analysis, Sentence structure